Familial screening of children with Wilson disease: Necessity of screening in previous generation and screening methods. Issue 27 (July 2018) - Li, Huamei; Liu, Lifang; Li, Yun; He, Shendi; Liu, Yujie; Li, Jinhong; Tao, Ran; Li, Wei; Shang, Shiqiang
Abstract : Abstract: Wilson disease (WD) is an autosomal recessive genetic disorder associated with copper metabolism. Early diagnosis and therapy can result in good prognosis of WD. Thus, it is highly recommended to perform familial screening. In this study, we aimed to investigate the range of familial screening of children with WD and determine the appropriate screening methods. We enrolled 20 children with WD and 50 family members of each of these patients (40 parents and 10 siblings). All the subjects underwent a physical examination, Kayser–Fleischer (K-F) rings in the cornea, abdominal ultrasonography (Abdl Ur), cranial magnetic resonance imaging (MRI), serum ceruloplasmin, serum copper, 24-hour urine copper, blood alanine transaminase (ALT) and aspartate transaminase (AST), and ATP7B gene. Two new patients with presymptomatic WD (1 mother and 1 brother) in 2 families were found by screening. They had no clinical symptoms and K-F rings in corneal. Biochemical examination indicated decreased serum ceruloplasmin and serum copper in the mother and decreased serum ceruloplasmin in the brother. Gene sequencing revealed compound heterozygous mutations in them. In addition, 48 heterozygous carriers of Wilson disease (WHDzc) were found in this study. The levels of ceruloplasmin and serum copper in patients of WD were significantly less than WHDzc and 24-hour urinary copper were significantly higher than WHDzc ( P = .000). The biochemical profiles of WD and WDHzc overlapped in range of 0.8 to 1.5 g/L in ceruloplasmin, above 9 μmol/L in serum copper and below 100 μg/24 h in urinary copper. Gene sequencing showed 2 pathological mutations in all patients with WD and 1 pathological mutation in all WDHzc. Not only siblings but also the previous generation of children probands with WD should be screened. Genetic testing should be conducted for the diagnosis of presymptomatic patients with WD.